Crystal structure of the Escherichia coli transcription termination factor Rho. Issue 9 (3rd September 2020) - Fan, Chengcheng; Rees, Douglas C.
Abstract : A structure is reported of the E. coli transcription terminator factor Rho that was crystallized as an impurity present in preparations of an overexpressed bacterial membrane‐transport protein. Abstract : During the crystal structure analysis of an ATP‐binding cassette (ABC) transporter overexpressed in Escherichia coli, a contaminant protein was crystallized. The identity of the contaminant was revealed by mass spectrometry to be the Escherichia coli transcription terminator factor Rho, structures of which had been previously determined in different conformational states. Although Rho was present at only ∼1% of the target protein (a bacterial homolog of the eukaryotic ABC transporter of mitochondria from Novosphingobium aromaticivorans ; Na Atm1), it preferentially crystallized in space group C 2 as thin plates that diffracted to 3.30 Å resolution. The structure of Rho in this crystal form exhibits a hexameric open‐ring staircase conformation with bound ATP; this characteristic structure was also observed on electron‐microscopy grids of the Na Atm1 preparation.